Yeasts and other culturable microorganisms associated with the nickel hyperaccumulator Berkheya coddii and its insect herbivore, Chrysolina clathrata - Postma, Ferdinand (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.